Buffering or not working: group counseling for depression and loneliness among boarding primary school students - Peng Wang; Junchi Ma; Longlong Du; Qiulian Xing; Xinyu Cheng; Mingzhu Zhang; Fei Geng; Yuanxin Zheng; Fangxiao Zheng; Mei Tian (Frontiers in Public Health)
IntroductionDue to the acceleration of modern life rhythm, students with developing minds are susceptible to negative external influences, leading to a growing concern for their mental health. Boarding primary school students have limited interaction with relatives compared to their non-boarding counterparts, rendering them more prone to feelings of depression and loneliness, resulting in various negative emotions. Therefore, our study aimed to explore the effects of group counseling interventions on reducing depression and loneliness among adolescents.MethodsThe study analyzed loneliness and depression before and after the intervention in eight randomly selected classes of fifth-grade students at a boarding school in a region of Shandong Province, which were divided into an experimental group and a control group.ResultsWithin the experimental group, there were no substantial variations in loneliness and depression levels. In the control group, post-test depression results significantly surpassed pre-test scores (p = 0.046), though loneliness levels did not differ significantly. Conversely, the experimental group displayed significantly reduced post-test depression levels compared to the control group (p = 0.037), with no significant variance in loneliness.ConclusionThe findings indicated that group psychological counseling mitigates depression in the experimental group to a certain extent, affirming the efficacy of the intervention. The study demonstrated that group counseling alleviates depression in boarding students, emphasizing the value of the intervention.